Mixed convection on MHD flow with thermal radiation, chemical reaction and viscous dissipation embedded in a porous medium - Zigta, Binyam (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a theoretical analysis has been made to study the effect of mixed convection MHD oscillatory Couette flow in a vertical parallel channel walls embedded in a porous medium in the presence of thermal radiation, chemical reaction and viscous dissipation. The channel walls are subjected to a constant suction velocity and free stream velocity is oscillating with time. The channel walls are embedded vertically in a porous medium.
Keywords: mixed convection; suction velocity; thermal radiation; chemical reaction; viscous dissipation